Neuro-inflammation, depression and fatigue in ESRD: Emerging role of microglia and acupuncture as a new treatment addressing neuro-inflammation in ESRD - Suandika Made; Handayani Rahmaya Nova; Muti Refa Teja (BIO Web of Conferences)
ESRD is the most serious form of CKD and is frequently associated with a variety of complications, including depression and fatigue. These diseases contribute to higher morbidity and death among ESRD patients. Chronic inflammation and other pathological factors contribute to the occurrence of both of the aforementioned consequences. The purpose of this study is to propose that neuroinflammation-induced microglial activation may play an important role in these circumstances. Their interplay also provides new avenues for improving palliative care. The method employed combines a literature review with a narrative review to provide an evaluation of the connection of low-grade systemic inflammation with depression and overload in ESRD patients. The findings of this review show that depressive symptoms and fatigue are common in ERDS patients. Acupuncture, as a non-pharmacological option, has been shown to reduce chronic inflammation and enhance clinical results for ERSD patients’ quality of life. In conclusion, acupuncture is showing promise as treatment because they can alter neuroinflammatory pathways and lessen symptoms.